Adsorption of Safranin‐O Dye Onto Almond Shell Sustainable Activated Carbon: Identifying Key Process Factors and Their Effects - Nawras J. Jassim; Fitna H. Younis; Maher T. Alshamkhani (Engineering Reports)
ABSTRACT Water pollution is a critical issue requiring urgent action to minimize contamination and ensure a sustainable future for humanity. Dyes are widely utilized in many industries, generating worries about water contamination. This study aimed to develop an inexpensive and sustainable process for safranin dye removal from polluted water using biomass waste. Almond shells were carbonized at a temperature of 500°C and then chemically activated using phosphoric acid to produce activated carbon. The activated carbon samples were analyzed using (XRD), (SEM), (EDX), N2‐adsorption–desorption isotherms, and (FTIR) analysis. Activated carbon was selected and evaluated for its ability to adsorb safranin dye from simulated wastewater. A definitive screening design DSC was utilized to quickly examine the impact of six adsorption process factors (initial dye concentration, pH, ionic strength, adsorbent dose, contact time, and ultrasonic power) on the adsorption capacity of safranin dye. A mathematical model was developed to determine the effect of each factor and the contribution and interactions between the factors on the adsorption capacity of safranin dye. The experimental results showed that the initial dye concentration, adsorbent dose, pH, and ultrasonic power effects were most important. In contrast, the contact time and ionic strength do not have a clear and significant impact. The outcomes were promising, wherein the maximum adsorption capacity of safranin‐O dye was 57.4 mg/g (25°C), 300 mg/L initial dye concentration,100 mg adsorbent dose, pH in the range 7–10, and 228‐W ultrasonic power. The adsorption experimental equilibrium data show that the Langmuir model is suitable for safranin‐O adsorption behavior. Kinetic experimental data showed that the adsorption processes followed pseudo‐second‐order. The reported results revealed that the DSD experimental design can be utilized to determine the essential and non‐essential factors in the batch adsorption process of safranin‐O by reducing time, cost, and number of experiments.